Transdentinal protective role of sodium ascorbate against the cytopathic effects of H2O2 released from bleaching agents - Lima, Adriano Fonseca; Rosetti Lessa, Fernanda Campos; Gasparoto Mancini, Maria Nadir [UNESP]; Hebling, Josimeri [UNESP]; de Souza Costa, Carlos Alberto [UNESP]; Marchi, Giselle Maria (Mosby-elsevier, 2010)
Objectives. The objectives of this study were to evaluate the transdentinal cytotoxicity of 10% and 16% carbamide peroxide gel (CP), as well as the ability of the antioxidant, 10% sodium ascorbate (SA), to protect the odontoblasts in culture.Study design. Human dentin discs of 0.5-mm thickness were obtained and were placed into artificial pulp chambers. MDPC-23 odontoblastlike cells were seeded on pulp surface of the discs and the following groups were established: G1-No Treatment (control), G2-10% SA/6hs, G3-10%/CP6hs, G4-10%SA/6hs+10%CP/6hs, G5-16%CP/6hs, and G6-10%SA/6hs+16%CP/6hs. The cell viability was measured by the MTT assay.Results. In groups where 16% CP was used, decreased cell viability was observed. Conversely, the application of 10% SA on the dentin discs, before the use of the CP, reduced the cytotoxic effects of these products on cells.Conclusions. The 16% CP cause a significant decrease in MDPC-23 cell viability and 10% SA was able to partially prevent the toxic effects of CP. (Oral Surg Oral Med Oral Pathol Oral Radiol Endod 2010; 109: e70-e76)